Experimental reconstruction of spatial Schmidt modes for a wide-field SU(1,1) interferometer - Frascella, Gaetano; Zakharov, Roman V.; Tikhonova, Olga V.; Chekhova, Maria (Laser Physics, 2019)
We study the spatial mode content at the output of a wide-field SU(1,1) interferometer, i.e. a nonlinear interferometer comprising two coherently-pumped spatially-multimode optical parametric amplifiers placed in sequence with a focusing element in between. This device is expected to provide a phase sensitivity below the shot-noise limit for multiple modes over a broad angular range. To reconstruct the spatial modes and their weights, we implement a simple method based on the acquisition of only intensity distributions. The eigenmode decomposition of the field is obtained through the measurement of the covariance of intensities at different spatial points. We investigate both the radial and azimuthal (orbital angular momentum) modes and show that their total number is large enough to enable applications of the interferometer in spatially-resolved phase measurements.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Orbital angular momentum; Parametric down-conversion; Schmidt modes; SU(1; 1) interferometer

Multimode optical parametric amplification in the phase-sensitive regime - Frascella, Gaetano; Zakharov, R. V.; Tikhonova, O. V.; Chekhova, Maria (Optics Letters, 2021)
Phase-sensitive optical parametric amplification of squeezed states helps to overcome detection loss and noise and thus increases the robustness of sub-shot-noise sensing. Because such techniques, e.g., imaging and spectroscopy, operate with multimode light, multimode amplification is required. Here we find the optimal methods for multimode phase-sensitive amplification and verify them in an experiment where a pumped second-order nonlinear crystal is seeded with a Gaussian coherent beam. Phase-sensitive amplification is obtained by tightly focusing the seed into the crystal, rather than seeding with close-to-plane waves. This suggests that phase-sensitive amplification of sub-shot-noise images should be performed in the near field. A similar recipe can be formulated for the time and frequency, which makes this work relevant for quantum-enhanced spectroscopy.
CRIS-Team Scopus Importer:2021-05-21

Optical coherence tomography with a nonlinear interferometer in the high parametric gain regime - MacHado, Gerard J.; Frascella, Gaetano; Torres, Juan P.; Chekhova, Maria (Applied Physics Letters, 2020)
We demonstrate optical coherence tomography based on an SU(1,1) nonlinear interferometer with high-gain parametric downconversion. For imaging and sensing applications, this scheme promises to outperform previous experiments working at low parametric gain, since higher photon fluxes provide lower integration times for obtaining high-quality images. In this way, one can avoid using single-photon detectors or CCD cameras with very high sensitivities, and standard spectrometers can be used instead. Other advantages are higher sensitivity to small loss and amplification before detection so that the detected light power considerably exceeds the probing one.
CRIS-Team Scopus Importer:2020-09-25

Orbital angular momentum modes of high-gain parametric down-conversion - Beltran, Lina; Frascella, Gaetano; Perez, Angela M.; Fickler, Robert; Sharapova, Polina R.; Manceau, Mathieu; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Journal of Optics, 2017)
Light beams with orbital angular momentum (OAM) are convenient carriers of quantum information. They can also be used for imparting rotational motion to particles and providing high resolution in imaging. Due to the conservation of OAM in parametric down-conversion (PDC), signal and idler photons generated at low gain have perfectly anti-correlated OAM values. It is interesting to study the OAM properties of high-gain PDC, where the same OAM modes can be populated with large, but correlated, numbers of photons. Here we investigate the OAM spectrum of high-gain PDC and show that the OAM mode content can be controlled by varying the pump power and the configuration of the source. In our experiment, we use a source consisting of two nonlinear crystals separated by an air gap. We discuss the OAM properties of PDC radiation emitted by this source and suggest possible modifications.
CRIS-Team Scopus Importer:2023-03-27
Keywords: bright squeezed vacuum; coherent modes; orbital angular momentum; parametric down-conversion; Schmidt modes

Overcoming detection loss and noise in squeezing-based optical sensing - Frascella, Gaetano; Agne, Sascha; Khalili, Farid Ya.; Chekhova, Maria (npj Quantum Information, 2021)
Among the known resources of quantum metrology, one of the most practical and efficient is squeezing. Squeezed states of atoms and light improve the sensing of the phase, magnetic field, polarization, mechanical displacement. They promise to considerably increase signal-to-noise ratio in imaging and spectroscopy, and are already used in real-life gravitational-wave detectors. But despite being more robust than other states, they are still very fragile, which narrows the scope of their application. In particular, squeezed states are useless in measurements where the detection is inefficient or the noise is high. Here, we experimentally demonstrate a remedy against loss and noise: strong noiseless amplification before detection. This way, we achieve loss-tolerant operation of an interferometer fed with squeezed and coherent light. With only 50% detection efficiency and with noise exceeding the level of squeezed light more than 50 times, we overcome the shot-noise limit by 6 dB. Sub-shot-noise phase sensitivity survives up to 87% loss. Application of this technique to other types of optical sensing and imaging promises a full use of quantum resources in these fields.
CRIS-Team WoS Importer:2021-05-21

Overcoming detection losses in a supersensitive interferometer with coherent and squeezed vacuum inputs - Frascella, Gaetano; Agne, Sascha; Khalili, Farid Ya; Chekhova, Maria (Optics InfoBase Conference Papers, 2020)
We report phase sensitivity overcoming the shot-noise limit by 3 dB for a squeezing-assisted interferometer with 50% detection losses. The performance is tolerant to losses up to 87% because of an optical parametric amplifier at the output.
CRIS-Team Scopus Importer:2020-11-13

Properties of bright squeezed vacuum at increasing brightness - Sharapova, P. R.; Frascella, Gaetano; Riabinin, M.; Perez, A. M.; Tikhonova, Olga; Lemieux, S.; Boyd, R. W.; Leuchs, Gerd; Chekhova, Maria (Physical Review Research, 2020)
A bright squeezed vacuum (BSV) is a nonclassical macroscopic state of light, which is generated through high-gain parametric down-conversion or four-wave mixing. Although the BSV is an important tool in quantum optics and has a lot of applications, its theoretical description is still not complete. In particular, the existing description in terms of Schmidt modes with gain-independent shapes fails to explain the spectral broadening observed in the experiment as the mean number of photons increases. Meanwhile, the semiclassical description accounting for the broadening does not allow us to decouple the intermodal photon-number correlations. In this work, we present a new generalized theoretical approach to describe the spatial properties of a multimode BSV. In the multimode case, one has to take into account the complicated interplay between all involved modes: each plane-wave mode interacts with all other modes, which complicates the problem significantly. The developed approach is based on exchanging the (k, t) and (omega, z) representations and solving a system of integrodifferential equations. Our approach predicts correctly the dynamics of the Schmidt modes and the broadening of the angular distribution with the increase in the BSV mean photon number due to a stronger pumping. Moreover, the model correctly describes various properties of a widely used experimental configuration with two crystals and an air gap between them, namely, an SU(1,1) interferometer. In particular, it predicts the narrowing of the intensity distribution, the reduction and shift of the side lobes, and the decline in the interference visibility as the mean photon number increases due to stronger pumping. The presented experimental results confirm the validity of the new approach. The model can be easily extended to the case of the frequency spectrum, frequency Schmidt modes, and other experimental configurations.
CRIS-Team WoS Importer:2021-01-15

Reconstructing two-dimensional spatial modes for classical and quantum light - Averchenko, Valentin A.; Frascella, Gaetano; Kalash, Mahmoud; Cavanna, Andrea; Chekhova, Maria (Physical Review A, 2020)
We propose a method for finding two-dimensional spatial modes of thermal field through a direct measurement of the field intensity and an offline analysis of its spatial fluctuations. Using this method, in a simple and efficient way we reconstruct the modes of a multimode fiber and the spatial Schmidt modes of squeezed vacuum generated via high-gain parametric down-conversion. The reconstructed shapes agree with the theoretical results.
CRIS-Team WoS Importer:2020-12-18

Wide-field SU(1,1) interferometer - Frascella, Gaetano; Mikhailov, E. E.; Takanashi, N.; Zakharov, R. V.; Tikhonova, O. V.; Chekhova, Maria (Optica, 2019)
An SU(1,1) interferometer uses a sequence of two optical parametric amplifiers for achieving sub-shot-noise sensitivity to a phase shift introduced in between. We present the first realization of a wide-field SU(1,1) interferometer, where the use of a focusing element enables spatially multimode operation within a broad angle. Over this angle, the interference phase is found to be flat. This property is important for the high sensitivity to the phase front disturbance. Further, -4.3 +/- 0.7 dB quadrature squeezing, an essential requirement to the high sensitivity, is experimentally demonstrated for plane-wave modes inside the interferometer. Such an interferometer is useful not only for quantum metrology, but also in remote sensing, enhanced sub-shot-noise imaging, and quantum information processing. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-10-11